2009
DOI: 10.5293/ijfms.2009.2.1.055
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of a Film Cooling System with Normal Injection Holes Using Experimental Data

Abstract: The present study investigated temperature and thermal stress distributions in a film cooling system with normal injection cooling flow. 3D-numerical simulations using the FEM commercial code ANSYS were conducted to calculate distributions of temperature and thermal stresses. In the simulations, the surface boundary conditions used the surface heat transfer coefficients and adiabatic wall temperature which were converted from the Sherwood numbers and impermeable wall effectiveness obtained from previous mass t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In other words, if an operation condition is unsuitable, local thermal cracks and structural failure may occur due to the high thermal stress. Therefore, a thermal analysis [9][10][11] and a failure analysis [12][13][14][15][16] are required for an effective thermal design.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, if an operation condition is unsuitable, local thermal cracks and structural failure may occur due to the high thermal stress. Therefore, a thermal analysis [9][10][11] and a failure analysis [12][13][14][15][16] are required for an effective thermal design.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to estimate the stress distributions and to predict the lifetime for the cooling system due to the safety of hot components, such as combustors, vanes, and blades. In recent years, Kim et al [10] and Lee et al [11] have studied the distributions of both temperature and thermal stress that are induced by convection and conduction in a film cooling system. They found that the highest temperature and stress appear in the cooling system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, accurate prediction of conjugated heat transfer distributions on external and internal metal surfaces is also important in cooling system designs for new concept and modification. Recently, many researchers [4][5][6][7] have investigated methodologies and characteristics of the conjugated heat transfer including conduction and convection. Thus thermal analysis becomes an important issue in order to enhance the heat transfer as well as to reduce the thermal stress yielded by temperature gradients.…”
Section: Introductionmentioning
confidence: 99%